Distributional Effects of CAP Subsidies: Micro Evidence from the EU - Pavel Ciaian; d'Artis Kancs; Sergio Gomez y Paloma (Economics and Econometrics Research Institute (EERI), 2010)
In this paper we estimate the income distributional effects of the common agricultural policy (CAP) for farmers and landowners. First, we theoretically analyse the level of farmers' and landowners' gains from coupled and decoupled payments. Second, using a unique farm level panel data set from the FADN for the period 1995-2007 we employ the fixed effects, the Heckman selection bias and the GMM estimators to estimate income distributional effects of CAP subsidies. The results do not confirm the theoretical hypothesis that landowners benefit a large share of the CAP subsidies. According to our estimates, farmers gain between 60% to 95%, 80% to 178% and 86% to 90% of the total value of coupled crop/animal, coupled RDP and decupled payments, respectively. The CAP subsidies are only marginally capitalised in land rents. Our results suggest that the rental rates are more responsive to structural variables and show a strong time dependency, suggesting the presence of rigidities in the EU rental markets, which constraint the adjustment of land rents to market signals and thus reduce landowners' gains from the CAP.
Keywords: F12; L11; Q11; Q12; Q15; Q18; P32; R12; R23; 330; Distributional effects; panel microdata; GMM; CAP; land rents